(untitled) (Nexo Revista Científica, 2026)
This article empirically evaluates the Dutch Disease hypothesis in Nicaragua in the face of the unprecedented boom in remittance inflows during the 2006-2023 period. To overcome overparameterization limitations and capture long-run equilibrium dynamics amidst structural breaks, a Bayesian Vector Error Correction Model (BVECM) is estimated. The Impulse-Response Functions (IRF) analysis dismisses the materialization of this macroeconomic syndrome in the Nicaraguan economy. First, there is no evidence of a detrimental "spending effect," as remittances do not significantly appreciate the Real Exchange Rate Index (ITCER). This shielding is attributed to the high marginal propensity to import and the administered exchange rate regime, which act as leakage valves. Second, the deindustrialization of the tradable sector is rejected; conversely, foreign currency shocks generate a transitory expansion in productive output by alleviating severe local liquidity and credit constraints. The study concludes that remittances act as a key macroeconomic stabilizer without eroding the country’s structural competitiveness.